ANALYSIS OF CONTROL SYSTEM RELIABILITY AT PLTG UPDK TELLO - Ardiansyah Al Izzah; A Lamada, Mustari; Zulhajji, Zulhajji; Imran, Al; T Mangesa, Riana (Journal of Electrical Engineering and Informatics, 2025)
This study analyzes the reliability of the control system at the UPDK Tello Gas Power Plant (PLTG) with a focus on critical components that affect systemperformance. The evaluation was conducted using three main indicators: availability, Mean Time to Failure (MTTF), and Mean Time to Repair (MTTR), andtheir impact on operational efficiency. Quantitative descriptive research method was applied through Failure Mode and Effects Analysis (FMEA) analysis, direct observation, and maintenance document study. The results showed variations in reliability between components. In GE#1, the TCDA card has the highest RPN value of 156, availability 0.9995435874, MTTF 13139.99999 hours, MTTR 5.999999999 hours, reliability 0.1353352832, and operationalefficiency 99.95431704%. At GE#2, the exhaust thermocouple has the highest RPN of 192 with a reliability of 0.04978706857, while the 1.5 A fuse has the lowest availability of 0.9994675591, MTTF of 26279.99999 hours, MTTR of 14 hours, and operational efficiency of 99.94672755%. The average operational efficiency at GE#1 and GE#2 are 99.9866758% and 99.98731608% respectively. The results show that the system still meets operating standards although there are significant differences between the RPN values and other reliability indicators. Components with high RPN do not always have the lowest availability or operational efficiency. This research emphasizes the importance of a multi-indicator approach in reliability analysis as well as the need for customized maintenance strategies for each critical component.